Recent changes to Arctic river discharge - Dongmei Feng (Nature Portfolio, 2021)
The authors combine satellite data with hydrologic models to investigate recent changes in pan-Arctic river discharge magnitude, trends, and seasonality for nearly half a million rivers. They reveal that these rivers likely exported 3-17% more water to the global ocean than previously thought from 1984-2018.